THE HISTORY OF HEALTHCARE IN KARAKALPAKSTAN IN 1924-1930 - Toreniyazov, Medet Turdibaevich (SCIENCE and SOCIETY, 2026)
This article analyzes the formation and development of the healthcare system in Karakalpakstan during the period 1924-1930. The study examines the implementation of the Soviet healthcare system in national peripheries, the fight against infectious diseases, and medical personnel training. Based on literature review and historical sources, the article considers the process of adapting the Soviet healthcare model to the conditions of Karakalpakstan.